Tālīm al-Lughah al-‘Arabīyah ḥaṣib al-Ta‘allum al-Qā’im ‘alā al-Mushkilah - Prabowo Adi Widayat (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
The problem is the result of the interaction between man and his environment. The problem has also become a part of the learning process of human beings to acquire knowledge and experience that is a notch better than ever. In addition, the problem became a matter of learning which occurs naturally through the daily live and that is formed through a mutual agreement for the themes of learning in learning and teaching activities. Problem based learning is a learning model that provides aspect of realistic problems that occur in life. On the other hand, a problem that is presented by form of contextualization learning materials are taught a process of discussion groups with interactive dialogue method. Furthermore, in the context of learning a foreign language, Arabic lesson also have relation problems realistically that can be seen through the Arabic proficiency such as listening, speaking, reading, and writing or knowledge of Arabic grammar is often studied and used to analyse and understand the Arabic books.